ثلاثية الحيوان في شعر امرئ القيس : دراسة تحليلية نقدية - نيوبيري، تامي سو (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
Pre-Islamic Arabic poetry is renowned for its vivid descriptions of the Jahiliyy environment. In particular, Imru' al-Qays, “The Torchbearer of Arabic poetry”, was famous for his detailing of the Camel and the Horse. These images have been fertile fields for numerous in-depth literary studies focusing on the effect of the poet's environment, both physical and cultural, on the construction of these icons. By contrast, relatively little study has been devoted to the study of other animal images in his works. In fact, this researcher has recognized amongst the animal tableaus is a recurrent triad of animals consisting of the Oryx, the Arabian Onager, and the Arabian Ostrich. The goals of this research are: to analyze the Oryx, Onager and Ostrich tableaus, and to establish that they are a coherent group. So too, it will point out the poetic devices, be they grammatical or environmental, which are employed in the context of the triad group of animal tableaus. Herein, it will seek to explain their effect on the text either a signal for duality of meaning or that a transition will be occurring in the scene; noting a change from realistic events to imaginary events and vice versa. Then, the differing scholarly opinions with regards to the realism or symbolism of animal images in Jahiliyy poetry will be put forth, as well as those scholarly opinions which explain the animals as adding a duality, or another dimension, to the poetry. The study concludes with an analysis of the applicability of the previous opinions on the triad of animal images in Imru' al-Qays poetry. Hereby, the substance of the animals is evaluated relative to the role which they play in the poetic image being conveyed in a particular section of the qasida.